Seasonal Dynamics and Diversity of Butterflies in Urban Parks of the Yamuna River Floodplain Area in Haryana, India - Vidisha Gupta; Kumar, Parmesh (Ecological Questions, 2025)
Urban parks provide crucial refuges for biodiversity within densely developed areas, supporting diverse butterfly communities. This study, conducted from March 2022 to February 2023 in five urban parks of Yamunanagar, Haryana, India, documented 1,306 butterflies across 45 species, 37 genera, and 5 families using the Pollard Walk method. Family Nymphalidae (17 species) showed the highest species richness, while Lycaenidae (458 individuals) was the most abundant family. Zizeeria karsandra (Dark Grass Blue) was the dominant species, with the top five species comprising nearly half of the total abundance. Spatio-temporal analysis using Bray–Curtis dissimilarity and hierarchical clustering revealed distinct patterns in butterfly assemblages across parks and seasons. Species richness and abundance followed a pronounced bimodal distribution, with peaks occurring during the summer and post-monsoon periods. Significant differences (P<0.05) in species richness, abundance, and diversity were observed both seasonally and spatially. SIMPER analysis identified five generalist species as primary contributors to inter-park dissimilarities. Principal Component Analysis indicated a positive association of species richness with temperature, and negative correlations with rainfall and humidity. Among the recorded species, eight were categorized as abundant and twelve as rare, including one Schedule II protected species (Euthalia aconthea) and three species listed as Least Concern by the IUCN. These results emphasize the role of urban park heterogeneity and climate in shaping butterfly diversity and identify key species for urban ecological monitoring.